Ore-genesis and evolution of the Pb-Zn-Ag-(Cu-Ba) deposits hosted by Perau Formation, southern Ribeira Belt, Brazil - Silva, Anderson Dourado Rodrigues da (2019)
The Canoas and Perau Pb-Zn-Ag- (Cu-Ba) deposits are located in the southeastern portion of the state of Paraná, near the border with the state of São Paulo, in a region called Vale do Ribeira. Various authors classify these as Sedex (sedimentary exhalative). The Ribeira Valley region has records of lead exploitation since the mid1950s, having been responsible for all Brazilian production in that period. This work investigated Canoas and Perau deposits by (1) compiling and integrating data from previous metallogenetic studies, (2) collecting new geological data in the field, (3) redescription of drill holes conducted by CPRM in the 1980s, (4) analyzes of sulfide mineral chemistry and sulfur isotopes in sulfides of the mineralized horizon, and (5) fluid inclusion studies in quartz of samples from the mineralized horizon. A Calymmian metavolcano-sedimentary succession (ca. 1475-1490 Ma), called the Perau Formation, dominates the geological framework of the Canoas and Perau deposits, which forms part of the Apiaí Terrane of the Southern Ribeira Belt, located in the central portion of the Mantiqueira Province. The Canoas and Perau deposits ore is characterized by massive and widespread sulfide levels consisting predominantly of the galenasphalerite-chalcopyrite-pyrite association, with varying amounts of barite along the mineralized horizon called \"Horizonte Perau\". The sulfide levels are intercalated in a package of calc-silicate rocks from the Perau Formation schist unit, which underwent deformation and metamorphism in high greenschist to amphibolite facies in the Neoproterozoic (615-570 Ma) during the Brasiliano / Pan African orogeny. Sulfur isotope data obtained for Canoas and Perau deposits (+1.2 to +13.16 ? and -1.88 to + 3.25 ?, respectively) show values similar to other Proterozoic-age SEDEX deposits with the sulfur source being dominated by seawater reduced by mechanisms of BSR (biogenic sulfate reduction) and TSR (thermochemical sulfate reduction). Analyzes of sphalerite mineral chemistry reveal differences in Fe content between barite (avg. 1.22 wt%) and silica (avg. 7.24 wt%) rich ores, indicating differences in sphalerite precipitation temperature between these two types of ore. Microthermometric data suggest the performance of metamorphic fluids characterized by primary fluid inclusions with intermediate Th (255 - 401 ° C) and low salinity (0.45 to 2.35% by weight of NaCl equiv.) and, by secondary aqueous inclusions with Th (108 - 203 ° C) and intermediate to high salinity values (6.44 to 25.33 wt% equiv. NaCl). The described fluids represent the H2O-NaCl-MgCl2-CO2 systems for the primary inclusions and H2O-NaCl-CaCl2 for the secondary aqueous inclusions. Both systems consist of chloride complexes, worked on the remobilization and, the reconcentration of primary mineralization during deformation and metamorphism in the Neoproterozoic.